Changes Of The Meaning In Arabic Words And Expressions On Students Daily Conversation - Sukkan Arya Putra (UIN ANTASARI, 2022)
Arabic is a language that is often used in modern Islamic boarding schools in Indonesia as a means of communication for students in their daily conversations. When Arabic is used among students as a communication tool, Arabic words or expressions arise that have changed from the meaning of fusha or from the initial meaning to meanings that other people, especially native speakers of the language cannot understand, except by the students themselves. Pondok Modern An Najah Putra is a Modern Islamic Boarding School educational institution that requires its students to use Arabic and English in daily conversation, this language obligation raises the phenomenon of changing meanings in sentences or expressions in the Arabic language they use which can only be understood by their environment. Therefore, this research is focused on changing Arabic words and expressions of the students of Pondok Modern An Najah Putra in daily conversation. To achieve this goal, the researcher uses a type of field research by using a descriptive qualitative approach to describe the facts that exist in the research area with the main subject of research changing meaning and the object of research is the words and expressions that exist in the students of Pondok Modern An Najah Putera. both verbally and written. The results of this study are words and expressions that have exchanged their meaning from the meaning of fusha or the initial meaning to other meanings that are only understood by students, forms of meaning exchange such as narrowing of meaning, expansion of meaning, and exchanges in new meanings with associations, exchanges in meaning. the meaning of mashdar to fi'il, exchanging the meaning of mashdar to ismul fa'il, exchanging the meaning of shifah musyabbah bi ismi al-fail to mashdar, exchanging the meaning of ismul fa'il to isim maf'ul, exchanging ismul maf'ul to fi'il, and exchanging harf to fi'il. Because the change in meaning is the influence of Indonesian in a variety of conversations, the emergence of the need for Arabic expressions, the influence of the Banjar language in various conversations, deviations in understanding Arabic, which is often used among students.